Autism Children and English Vocabulary Learning: A Qualitative Inquiry of the Challenges They Face in Their English Vocabulary Learning Journey - Haida Umiera Hashim; Melor Md Yunus; Helmi Norman (MDPI AG, 2022)
Language learning is one of the most important aspects of an individual's life development and growth. Normal learners' English language acquisition differs depending on their preferences and learning styles. Children with autism, on the other hand, appear to have different learning methods and routines. There has been a lot of previous work on the language learning styles of normal learners, but not much on the language learning path of children with autism. Due to that, this study aims at investigating the challenges children with autism face in their English vocabulary learning. Observations and focus group discussions were conducted with 45 children with autism, 4 autism education teachers, 2 occupational therapists and a parent of children with mild autism children to investigate the challenges autism children face in their vocabulary learning. The findings have gathered that autistic children encounter a few challenges occasionally in their English vocabulary learning journey. The data were gathered and arranged thematically. Further recommendations and suggestions are discussed in this study.